2020
DOI: 10.1021/acsanm.0c00973
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area Aligned Fullerene Nanocrystal Scaffolds as Culture Substrates for Enhancing Mesenchymal Stem Cell Self-Renewal and Multipotency

Abstract: Development of human mesenchymal stem cell (hMSC)-based therapies is hindered by the limited availability of adult stem cells. Long-term retention of multipotency and stemlike phenotypes remains a key challenge in the large-scale in vitro expansion process. In this paper, we report the primary example of the use of highly aligned fullerene nanowhisker nanopatterned scaffolds to regulate precisely adhesion and function of hMSCs. Continuously tunable alignment of fullerene nanowhiskers was attained using a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…This strategy was recently applied to regulate human mesenchymal stem cells for their enhanced renewal capability and multipotency where aligned one-dimensional fullerene nanowhiskers o a solid surface worked as a large area scaffold for cell culture (Figure 22). 79 In this approach, fullerene nanowhiskers with different aspect ratios were first prepared at the interface between m-xylene and isopropyl alcohol upon changing speeds of the addition of isopropyl alcohol onto C 60 mxylene solution. The fabricated fullerene nanowhisker materials were then subjected to the LB process to produce highly aligned arrays of one-dimensional C 60 nanowhiskers on a glass plate.…”
Section: Fate Control Of Living Cellmentioning
confidence: 99%
“…This strategy was recently applied to regulate human mesenchymal stem cells for their enhanced renewal capability and multipotency where aligned one-dimensional fullerene nanowhiskers o a solid surface worked as a large area scaffold for cell culture (Figure 22). 79 In this approach, fullerene nanowhiskers with different aspect ratios were first prepared at the interface between m-xylene and isopropyl alcohol upon changing speeds of the addition of isopropyl alcohol onto C 60 mxylene solution. The fabricated fullerene nanowhisker materials were then subjected to the LB process to produce highly aligned arrays of one-dimensional C 60 nanowhiskers on a glass plate.…”
Section: Fate Control Of Living Cellmentioning
confidence: 99%
“…Very recently, Song et al successfully demonstrated the culture system for human mesenchymal stem cells both capable of enhanced self‐renewal properties and retained multipotency using a solid interface covered with aligned fullerene nanowhiskers by the LB method ( Figure ). [ 111 ] Well optimized contact of human mesenchymal stem cells on hydrophobic surface of nanoarchitectured nanocarbon arrays resulted in certain extent of suppression of focal adhesions with small cytoskeletal tension, which is advantageous for long‐term retention of multipotency and expansion capability for human mesenchymal stem cells.…”
Section: Evolution From Atom/molecule To Materials With Nanoarchitectomentioning
confidence: 99%
“…demonstrated enhancement of self‐renewal capability and multipotency of mesenchymal stem cells through cell cultures on a solid surface covered with aligned fullerene nanowiskers. [ 59 ] For stem‐cell‐based therapies, long‐term retention of multipotency and stem‐like phenotypes are required key functions. Aligned structures of 1D hard nanocarbon of fullerene nanowiskers significantly influenced cell growth behaviors including spreading, orientation, and focal adhesions, leading to self‐renewal of mesenchymal stem cells.…”
Section: Cell Regulation By Interfacial Naturementioning
confidence: 99%